Liberalizing Home-Based Business - Agarwal, Sumit; Sing, Tien Foo; Song, Changcheng; Zhang, Jian (Management Science, 2024)
Working at home benefits entrepreneurs by lowering fixed costs and allowing them to engage in joint market and household production. We evaluate a large-scale reform in Singapore, the Home Office Scheme, that allowed business creation at one’s residential property and study whether home-based entrepreneurship spurs entrepreneurial activities. The difference-in-differences estimate shows that the reform led to a significantly higher level of business creation and the firms newly created in response to the reform had a higher survival rate. The effect is more pronounced for low-income female individuals and industries with high start-up capital, implying that financial constraints and nonpecuniary benefits likely drive the effect. The reform also encourages entrepreneurs to become serial entrepreneurs, and they open a larger business with a similar survival rate for their second firm. Overall, our findings suggest that the program effectively attracted more entry into self-employment without significantly lowering the average quality of the pool. This paper was accepted by David Sraer, finance. Funding: J. Zhang acknowledges support from the Seed Fund for Basic Research for New Staff of HKU [Code: 202009185022] and the General Research Fund by University Grants Committee of Hong Kong SAR [Grant 12500420]. Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2021.04232 .